Contribution of Extracellular Matrix and Signal Mechanotransduction to Epithelial Cell Damage in Inflammatory Bowel Disease Patients: A Proteomic Study. Issue 23 (29th November 2017) - Moriggi, Manuela; Pastorelli, Luca; Torretta, Enrica; Tontini, Gian Eugenio; Capitanio, Daniele; Bogetto, Stefano Ferrero; Vecchi, Maurizio; Gelfi, Cecilia
Abstract: This study utilizes 2D‐DIGE (difference gel etrophoresis), isotope‐coded protein labeling and biochemical assays to characterize protein alteration in ulcerative colitis (UC) and Crohn's disease (CD) in human epithelial cell and mucosal biopsies in inflammatory bowel disease (IBD)‐affected patients. The aim of this study is to identify the key molecular signatures involved in epithelial cell structure of IBDs. In non‐inflamed UC (QUC) keratins, vimentin, and focal adhesion kinase (7) increased, whereas vinculin and de‐tyrosinated α‐tubulin decreased; inflammation (IUC) exacerbated molecular changes, being collagen type VI alpha 1 chain (COL6A1), tenascin‐C and vimentin increased. In non‐inflamed CD (QCD), tenascin C, de‐tyrosinated α‐tubulin, vinculin, FAK, and Rho‐associated protein kinase 1 (ROCK1) decreased while vimentin increased. In inflamed CD (ICD), COL6A1, vimentin and integrin alpha 4 increased. In QUC, cell metabolism is characterized by a decrease of the tricarboxylic acid cycle enzymes and a decrease of short/branched chain specific acyl‐CoA dehydrogenase, fatty acid synthase, proliferator‐activated receptors alpha, and proliferator‐activated receptors gamma. In QCD a metabolic rewiring occurs, as suggested by glycerol‐3‐phosphate dehydrogenase (GPD2), pyruvate dehydrogenase E1 component subunit beta, NADH dehydrogenase [ubiquinone] iron‐sulfur protein 3, and 4‐trimethylaminobutyraldehyde dehydrogenase increment, while dihydrolipoyl dehydrogenase decreased. Macroautophagy is activated in QUC and IUC, with increased levels of p62, HSC70, major vault protein, myosin heavy chain 9, whereas it is blunted in QCD and ICD. The differing pattern of extracellular matrix, cytoskeletal derangements, cellular metabolism, and autophagy in UC and CD may contribute to the pathophysiological understanding of these disorders and serve as diagnostic markers in IBD patients.